2019
DOI: 10.1155/2019/9814537
|View full text |Cite
|
Sign up to set email alerts
|

LC-ESI-MS/MS Phenolic Profile of Volutaria lippii (L.) Cass. Extracts and Evaluation of Their In Vitro Antioxidant, Antiacetylcholinesterase, Antidiabetic, and Antibacterial Activities

Abstract: Volutaria lippii (L.) Cass., an indigenous perennial herb from the Tunisian flora, belongs to the medicinally important genus Volutaria Cass. (Asteraceae) which comprises eighteen species widely distributed in the Irano-Turanian and Mediterranean Basin. In this study, five different extracts from Tunisian Volutaria lippii (L.) Cass. were evaluated for their in vitro antioxidant, antiacetylcholinesterase, antidiabetic, and antibacterial activities as well as for their total phenolic and flavonoid contents. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…This results in damage to DNA, proteins, and lipids in cells, leading to cancer, hypertension, hyperlipidemia, or atherosclerosis. Antioxidants can block lipid chain autoxidation and provide hydrogen to free radicals, especially lipid peroxides, thus forming stable free radicals that do not initiate or induce further lipid oxidation ( Ben Salah et al, 2019 ). The antioxidant properties of phytochemicals, such as flavonoids, may have a similar effect.…”
Section: Iron Overload: An Imbalance Iron Metabolism That Causes Chronic and Common Diseasesmentioning
confidence: 99%
“…This results in damage to DNA, proteins, and lipids in cells, leading to cancer, hypertension, hyperlipidemia, or atherosclerosis. Antioxidants can block lipid chain autoxidation and provide hydrogen to free radicals, especially lipid peroxides, thus forming stable free radicals that do not initiate or induce further lipid oxidation ( Ben Salah et al, 2019 ). The antioxidant properties of phytochemicals, such as flavonoids, may have a similar effect.…”
Section: Iron Overload: An Imbalance Iron Metabolism That Causes Chronic and Common Diseasesmentioning
confidence: 99%
“…The compound 4 MS 2 mass spectrums showed fragments at m/z 463 [M‐H‐rhamnosyl] − and 301[M‐H‐rhamnosyl‐glucosyl] − (Figure 3). These results revealed that compound 4 was a rutin (Ben Salah et al, 2019). In addition, compound 6 had a deprotonated molecule [M‐H] ‐ at m/z 447, and a strong fragment at m/z 285 suggested that this compound was the luteolin‐7‐ O ‐glucoside.…”
Section: Resultsmentioning
confidence: 92%
“…LC‐ESI‐MS analysis was performed in order to increase the nutritional value of P. halepensis Mill. The identification of the phenolic compounds was carried out by mass spectra, comparison with reference compounds and with literature data (Rigane et al., 2011; Rigane et al., 2013; Boukhris et al., 2013; Ben Salah et al, 2019; Ben Hmed et al., 2020). Table 3 illustrates all the identified peaks with retention times, the pseudomolecular ions, as well as the concentration of each identified phenolic compound.…”
Section: Resultsmentioning
confidence: 99%
“…e chemical composition of the two Eucalyptus marginata L. extracts obtained after maceration and ultrasound-assisted extraction parameters was analyzed with LC-ESI-MS in the negative mode (Figure 5). Based on the mass spectra and comparison with reference compounds and with literature data [4,6,7,[37][38][39], the detected compounds were classified as phenolic acids such as quinic, gallic, protocatechuic, pcoumaric, salviolinic, trans-ferulic, and trans-cinnamic acids and flavonoids such as hyperoside, rutin, quercetrin, naringin, quercetin, and naringenin. Retention times, pseudomolecular ions, and the concentration of each identified phenolic compound are given in Table 4.…”
Section: Identification and Quantification Of Phenolic Compounds In Eucalyptus Marginata L Extractmentioning
confidence: 99%
“…Eucalyptus marginata is easily recognized by its flowers and fruits. Many research studies showed that the antioxidant activity, which is generally attributed with the interesting phenolic composition, allows this plant to be widely used in food and pharmaceutical industries [1][2][3][4][5][6][7]. Previous work showed that Eucalyptus is like any medicinal plant present an original chemical composition.…”
Section: Introductionmentioning
confidence: 99%